Standardization of Methodology to Determine Nitrogen, Total Reducing Sugar, Crude Lipid and Urea Content in Panchgavya Formulation - Maji, Soma; Rao, Priyanka Singh; Ramu, N.; Arora, Sumit; Sharma, Vivek (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted ICAR-National Dairy Research Institute, Karnal, Haryana, India during the year 2016−2020 to standardize the methodology to analyse the composition of panchgavya. Direct raw ingredients (milk urine and dung) were collected from live stock research centre, NDRI Karnal while indirect raw ingredients curd and ghee were prepared in laboratory. Panchgavya was prepared in three ratios i.e. RA, RB and RC by changing the level of urine and dung in final formulation. The methods for determination of nitrogen, crude lipid, reducing sugar and urea in panchgavya formulation were standardized. For all the analysis first theoretical value was calculated based on their percent in raw materials and experimental value was compared with it. Effect of sample weight and different methods to analyse composition was compared. In conclusion, it was found that Kjeldahl method for nitrogen content, Mojonnier acid digestion method for crude lipid, colorimetric method for lactose and DMAB (p- dimethyl amino benzaldehyde) for urea can be used as standard methods in the panchgavya formulation.